2019
DOI: 10.3233/jnd-190388
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Rater Reliability and Concurrent Validity of Quantified Muscle Testing for Maximal Knee Extensors Strength in Men with Myotonic Dystrophy Type 1

Abstract: BACKGROUND: Myotonic dystrophy type 1 (DM1) is the most prevalent degenerative neuromuscular disease in adults. Knee extensor (KE) maximal strength loss is a strong indicator of physical limitations in DM1. A reliable, precise and accessible maximal strength evaluation method needs to be validated for this slowly progressive disease. OBJECTIVE: This paper aims to assess the intra-rater reliability, the standard error of measurement (SEM), the minimal detectable change (MDC), and the concurrent validity of quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Optimizing muscle strength testing is important to optimize the evaluation of efficacy of new MND therapies and to contribute to the delivery of remote care [20]. In the field of voluntary muscle strength testing, the Biodex system is considered to be the gold standard [21,37,38] [16,39] These rigid frameworks are, however, not portable, require visits to the out-patient department, and are still operated by a trained examiner. Other methods that are applied to fixate dynamometers are belt or clamp fixations and stabilization devices [18,37,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing muscle strength testing is important to optimize the evaluation of efficacy of new MND therapies and to contribute to the delivery of remote care [20]. In the field of voluntary muscle strength testing, the Biodex system is considered to be the gold standard [21,37,38] [16,39] These rigid frameworks are, however, not portable, require visits to the out-patient department, and are still operated by a trained examiner. Other methods that are applied to fixate dynamometers are belt or clamp fixations and stabilization devices [18,37,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The handheld dynamometer used was the MEDup™ linear electronic handheld dynamometer (Atlas medic, Québec, Canada). QMT has shown evidence of reliability and validity for knee extension in the DM1 population 25 . For each muscle group, at least two trials were done: if results differed by more than 10%, a third or fourth trial was done.…”
Section: Methodsmentioning
confidence: 99%
“…QMT has shown evidence of reliability and validity for knee extension in the DM1 population. 25 For each muscle group, at least two trials were done: if results differed by more than 10%, a third or fourth trial was done. The mean of the two closest trials for each side was kept.…”
Section: Independent Variables and Covariatesmentioning
confidence: 99%
“…From the 39 studies that used quantitative muscle test, 17 studies did not report the method used [57,[68][69][70]73,[75][76][77][78][79]81,82,85,86,107,108,110], ten studies assessed maximum isometric torque [53,59,62,63,65,[70][71][72]79,108], seven studies assessed maximal voluntary isometric contraction [54,55,58,66,67,73,87] Maximal voluntary isometric contraction was used to assess the strength of Abductor digiti minimi [54], ankle dorsiflexors [58,87], ankle plantar flexors [87], grip strength [56,66,67], elbow flexors [73], elbow extensors [73], hip abductors [87], hip extensors [87], knee extensors [58, 73,87], knee flexors [73,87] and pinch strength [56]. Maximal voluntary isometric contraction results were between...…”
Section: Quantitative Muscle Testmentioning
confidence: 99%
“…Only 17 studies reported on longitudinal data: a cardiac study [105], 14 skeletal muscle strength studies [55,59,61,62,68,70,71,72,76,79,80,81,86,105], and two respiratory muscle strength studies [88,93].…”
Section: Muscle Strength Analysis In Longitudinal Studiesmentioning
confidence: 99%